Advancing Kashkadarya Research Station: Performance Insights for Agricultural Innovation - Dhehibi, Boubaker; Mylie, Obidjon; Souissi, Asma; Akramov, Kamiljon; Akramkhanov, Akmal; M. Oumer, Ali; Al-Zu'bi, Maha; Haddad, Mira; Crichton, Rhiannon; Baum, Michael (2024)
This technical report offers an in-depth evaluation of the Southern Agriculture Scientific Research Institute (SASRI) in Uzbekistan, emphasizing its pivotal role in driving agricultural innovation and sustainability in the Kashkadarya region. Operating at the nexus of research, practice, and policy, SASRI has established itself as a linchpin in Uzbekistan's efforts to bolster food security, adapt to climate challenges, and enhance agricultural productivity.